The Importance of Learning Islamic Religious Education to Shape Students' Morals at PAB 8 Saentis Private High School - Ramadhan, Rizky Awallul; Setiawan, Hasrian Rudi (Edumaniora : Jurnal Pendidikan dan Humaniora, 2022)
This study raises the issue of the importance of learning Islamic Religious Education to shape students' morals. The subjects of this study were students from SMA PRIVATE PAB 8 SAENTIS. This research was conducted in August 2022. The method used is the observation method. The results of this study indicate that the learning process at SMA PAB 8 SAENTIS has been running quite effectively in accordance with the basic concepts of the learning process carried out by most educators in general, namely students who follow the learning process enthusiastically, especially in learning . Islamic Education course. The method used by teachers of Islamic Religious Education subjects is the method of lectures, discussions, questions and answers, and assignments. However, the results of this study are not in line with expectations, even though the implementation of the learning process has been running according to the basic procedures that have been set. However, the morals of the santri and female students still cannot be said to be good, even though only some of them show an attitude that is not in accordance with Islamic Religious Education.